“Make it possible for more people to work at home!” representations of employee motivation and job satisfaction in Danish and Norwegian newspapers during the COVID-19 pandemic - Sonnenschein, Katrine; Hagen, Øivind; Rostad, Ingrid Steen; Wiik, Ragnhild (Frontiers in Psychology, 2022)
During the Covid-19 pandemic, many employees with task-based jobs were forced to work from home, while others were furloughed or laid off. The current study aims to investigate how Norwegian and Danish newspapers represent employee motivation and job satisfaction of remote workers in light of the Covid-19 pandemic. The study used a thematic analysis of five newspapers from Norway and Denmark with different daily distributions and political orientations. The findings suggest that the newspapers in the two countries represented the motivation and job satisfaction of employees working from home during the pandemic from different perspectives, and this led to the use of two motivation theories: the self-determination theory (SDT) and Herzberg’s two-factor theory. The SDT helps us understand why some employees feel motivated and are more productive while working from home. The need for autonomy, competence and connectedness is being satisfied for some employees but not for all, which may affect the strength of employees’ job motivation. Herzberg’s theory helps explain physical and psychological issues as dissatisfiers, as these issues are the consequence of working in a home-based office. Furthermore, it is important to recognise that people are individuals and not a homogenous group and therefore a hybrid model seems to be an optimal solution for the future job market, where employees with task-based jobs can feel motivation and job satisfaction working either from home or from the workplace. Finally, it is important for employers to look after both the physical and the psychosocial conditions if hybrid solutions are going to replace the traditional workplace.